Menjerat Kader, Melepas Partai Politik; Pertanggungjawaban Pidana Partai Politik Dalam Kasus Tindak Pidana Korupsi - Zulkifli Aspan; Wiwin Suwandi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2020)
Amid the resounding steps of the KPK to carry out the law enforcement function of eradicating Corruption, there are still things that feel stagnant. The KPK does not or has not dared to ensnare political parties in corrupt criminal liability, using corruption laws. In each case with dimensions of political corruption, the KPK only ensnares party elites, but does not at the same time demand criminal liability from political parties. In fact, in several cases investigated, the flow of funds flowed into political parties. As a special offense, revising the Corruption Law, by entering the phrase "legal entity", in addition to the phrase "everyone" is needed to find, or build a channel to ensnare political parties in corruption criminal liability. accompanied by state losses and fines. Administrative sanctions can also be applied through freezing through the Kemenkumham or the dissolution of these political parties through the Constitutional Court's path when the KPK's charges and demands can be proven.